Safety and efficacy of intrathecal antibodies to Nogo-A in patients with acute cervical spinal cord injury: a randomised, double-blind, multicentre, placebo-controlled, phase 2b trial - Weidner, Norbert; Abel, Rainer; Maier, Doris; Röhl, Klaus; Röhrich, Frank; Baumberger, Michael; Hund-Georgiadis, Margret; Saur, Marion; Benito-Penalva, Jesús; Rehahn, Kerstin; Aach, Mirko; Badke, Andreas; et al. (The lancet, 2025)
Background - Spinal cord injury results in permanent neurological impairment and disability due to the absence of spontaneous regeneration. NG101, a recombinant human antibody, neutralises the neurite growth-inhibiting protein Nogo-A, promoting neural repair and motor recovery in animal models of spinal cord injury. We aimed to evaluate the efficacy of intrathecal NG101 on recovery in patients with acute cervical traumatic spinal cord injury. - Methods - This randomised, double-blind, placebo-controlled phase 2b clinical trial was done at 13 hospitals in the Czech Republic, Germany, Spain, and Switzerland. Patients aged 18-70 years with acute, complete or incomplete cervical spinal cord injury (neurological level of injury C1-C8) within 4-28 days of injury were eligible for inclusion. Participants were initially randomly assigned 1:1 to intrathecal treatment with 45 mg NG101 or placebo (phosphate-buffered saline); 18 months into the study, the ratio was adjusted to 3:1 to achieve a final distribution of 2:1 to improve enrolment and drug exposure. Randomisation was done using a centralised, computer-based randomisation system and was stratified according to nine distinct outcome categories with a validated upper extremity motor score (UEMS) prediction model based on clinical parameters at screening. Six intrathecal injections were administered every 5 days over 4 weeks, starting within 28 days of injury. Investigators, study personnel, and study participants were masked to treatment allocation. The primary outcome was change in UEMS at 6 months, analysed alongside safety in the full analysis set. The completed trial was registered at ClinicalTrials.gov, NCT03935321. - Findings - From May 20, 2019, to July 20, 2022, 463 patients with acute traumatic cervical spinal cord injury were screened, 334 were deemed ineligible and excluded, and 129 were randomly assigned to an intervention (80 patients in the NG101 group and 49 in the placebo group). The full analysis set comprised 78 patients from the NG101 group and 48 patients from the placebo group. 107 (85%) patients were male and 19 (15%) patients were female, with a median age of 51·5 years (IQR 30·0-60·0). Across all patients, the primary endpoint showed no significant difference between groups (with UEMS change at 6 months 1·37 [95% CI -1·44 to 4·18]; placebo group mean 19·20 [SD 11·78] at baseline and 30·91 [SD 15·49] at day 168; NG101 group mean 18·23 [SD 15·14] at baseline and 31·31 [19·54] at day 168). Treatment-related adverse events were similar between groups (nine in the NG101 group and six in the placebo group). 25 severe adverse events were reported: 18 in 11 (14%) patients in the NG101 group and seven in six (13%) patients in the placebo group. Although no treatment-related fatalities were reported in the NG101 group, one fatality not related to treatment occurred in the placebo group. Infections were the most common adverse event affecting 44 (92%) patients in the placebo group and 65 (83%) patients in the NG101 group. - Interpretation - NG101 did not improve UEMS in patients with acute spinal cord injury. Post-hoc subgroup analyses assessing UEMS and Spinal Cord Independence Measure of self-care in patients with motor-incomplete injury indicated potential beneficial effects that require investigation in future studies. - Funding - EU program Horizon2020; Swiss State Secretariat for Education, Research and Innovation; Wings for Life; the Swiss Paraplegic Foundation; and the CeNeReg project of Wyss Zurich (University of Zurich and Eidgenössische Technische Hochschule Zurich).
Gesehen am 27.01.2025
Korrigierte Version: 10. Januar 2025
Online verfügbar: 18. Dezember 2024